Differences between users and non-users of complementary and alternative medicine among people with multiple sclerosis in Denmark: A comparison of descriptive characteristics. Issue 5 (July 2013) - Skovgaard, Lasse; Nicolajsen, Peter Halkier; Pedersen, Elena; Kant, Matthias; Fredrikson, Sten; Verhoef, Marja; Meyrowitsch, Dan
Aims : The aim of this study was to investigate differences in socio-economic characteristics between CAM users and CAM non-users among people with MS in Denmark as well as differences in characteristics related to the use of CAM among CAM users and the use of conventional treatments among CAM non-users. Methods : An internet-based questionnaire was used to collect data from 3361 patient members of the Danish MS society. A letter with a personal code was sent to all respondents, asking them to fill out the questionnaire online. Reminders to non-respondents were sent twice and the final response rate was 55.5%. Statistical associations were presented as odds ratios and with respective 95% confidence intervals. Results : People with MS in Denmark use a wide range of CAM treatments for a variety of reasons. CAM users were more likely to be of female gender, 18–40 years of age, educated at bachelor level or above, and have a high income compared to CAM non-users ( p < 0.05). CAM users more often addressed non-specific/preventive treatment purposes through their use of CAM treatments, they communicated less often with a medical doctor about the CAM treatments used, and they experienced less side effects as well as less positive effects from the CAM treatments used when compared with the use of conventional treatments among CAM non-users ( p < 0.05). Conclusions : People with MS in Denmark reported use of a large range of CAM treatments. CAM users differed from CAN non-users in relation to socio-economic factors as well as treatment characteristics.